Мешок, который устаёт : сказки для семейного чтения : на удм. яз / В. Н. Ившин ; худ. О. В. Санников - Ившин Вениамин Никонорович (Удмуртия, 2012)
Экземпляры: ДО (20150203) / Инвентарный номер: 34892 / Цена: 91.25 / Авт.знак: И 25 / ББК: 84 (2Рос=Удм)